2017
DOI: 10.4314/jab.v116i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of pod yield and 100 seeds weight in peanut (<i>Arachis hypogaea</i> L.) using GRIFFING and HAYMAN methods.

Abstract: Neya et al., J. Appl. Biosci. 2017 Diallel analysis of pod yield and 100 seeds weight in peanut (Arachis hypogaea L.) using GRIFFING and HAYMAN methods. 11619Journal of Applied Biosciences 116: 11619-11627 ISSN 1997-5902 Diallel analysis of pod yield and 100 seeds weight in peanut (Arachis hypogaea L.) using GRIFFING and HAYMAN methods. ABSTRACT Objectives: The lack of information on yield and yield components are an obstacle in peanut (Arachis hypogaea L.) breeding for productivity improvement in BURKIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Diallel random model, analysis showing general combining ability significantly indicates that traits are more influenced by additive gene effect, the analysis that showing significant specific combining ability indicates traits are more influenced by non-additive gene effect. Traits that have a greater general combining ability variance than specific combining ability are thought to be more influenced by additive genes (Fasahat et al 2016), the traits with general combining ability are indicated traits more influenced by additive gene effect, which is weight of 100 seed, number of seeds per pod and number of pods per bunch are different from the results obtained on peanuts (Neya et al 2017) the weight of 100 seeds is influenced by the effects of non-additive genes Similar results were reported by Idahosa and Alika (2013) in cowpea for 100 characters of seed weight which were influenced by additive and non additive effects. The pods reported by Neya et al (2017) were more influenced by the effects of additive genes obtained from the results of GCA / SCA ratios greater than 1 while in the Idahosa and Alika (2013) results obtained that the number of seeds per pod was influenced by the additive gene effect and the non-additive that can be predicted from significant value of the general combining ability and specific combining ability according to Medici et al (2004) significant general combining ability indicates that at least one of the results of the crossing affected by the effects of additive genes while significant specific combining ability indicates that at least one of the elders affected by the effect of a non-additive gene or the observed traits affected by more than one locus.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Diallel random model, analysis showing general combining ability significantly indicates that traits are more influenced by additive gene effect, the analysis that showing significant specific combining ability indicates traits are more influenced by non-additive gene effect. Traits that have a greater general combining ability variance than specific combining ability are thought to be more influenced by additive genes (Fasahat et al 2016), the traits with general combining ability are indicated traits more influenced by additive gene effect, which is weight of 100 seed, number of seeds per pod and number of pods per bunch are different from the results obtained on peanuts (Neya et al 2017) the weight of 100 seeds is influenced by the effects of non-additive genes Similar results were reported by Idahosa and Alika (2013) in cowpea for 100 characters of seed weight which were influenced by additive and non additive effects. The pods reported by Neya et al (2017) were more influenced by the effects of additive genes obtained from the results of GCA / SCA ratios greater than 1 while in the Idahosa and Alika (2013) results obtained that the number of seeds per pod was influenced by the additive gene effect and the non-additive that can be predicted from significant value of the general combining ability and specific combining ability according to Medici et al (2004) significant general combining ability indicates that at least one of the results of the crossing affected by the effects of additive genes while significant specific combining ability indicates that at least one of the elders affected by the effect of a non-additive gene or the observed traits affected by more than one locus.…”
Section: Discussionmentioning
confidence: 84%
“…Yield component consists of 100 seeds weight, number of seeds per pod, number of pods per bunch, number of pods per plant, and yield per plant (Table 3). In the analysis of variance, it was found that the general combining ability (GCA) the weight of 100 seeds was significant at 0.01 level, whereas in peanuts (Neya et al 2017) the results showed that the weight of 100 seeds has been significant at specific combining ability (SCA). The number of seeds per pod was significant at the 0.01 level different from the results of the study by Dahosa and Alika (2013), the number of seeds per pod has been significant value, in B I O D I V E R S I T A S 20 (5): 1294-1298, May 2019 1296 general, combining ability (GCA) and specific combining ability (SCA) while in peanut (Jogloy et al 2005), the yield character pods, seed yield, and weight of 100 seeds have been significant in general combining ability (GCA).…”
Section: Combining Ability Yield Componentmentioning
confidence: 96%
“…Diallel crosses and combining ability studies provides an opportunity to know the mode of inheritance and provide a clear concept for breeders to understand the basis on which certain parental traits could be exploited in the breeding programme. Additionally, general combining ability (GCA), specific combining ability (SCA) variance provides breeders an insight on additive and non-additive inheritance, respectively where reciprocal combining ability (RCA) signify the maternal effect (13). Heterosis study also helps the breeder to assess the superiority and inferiority of the F1 hybrids as compared to their parents and also for selecting suitable parents for achieving higher genetic gain.…”
Section: Introductionmentioning
confidence: 99%
“…Most research results are confined to annual reports of individual projects with little published in international journals [25]. To our knowledge, publications in recent years have focused mainly on yield evaluation [26] and disease of local and exotic varieties for early leaf spot [27,28]. Earlier research activities involved the evaluation of resistance to foliar diseases in lines introduced from ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) or the USA through the Peanut CRSP (Peanut Collaborative Research Support Program) [29][30][31] and similar development programmes.…”
Section: Introduction: the Importance Of Groundnut In Burkina Fasomentioning
confidence: 99%